Maritime ecosystem-based management in practice: Lessons learned from the application of a generic spatial planning framework in Europe. (January 2017) - Buhl-Mortensen, Lene; Galparsoro, Ibon; Vega Fernández, Tomás; Johnson, Kate; D'Anna, Giovanni; Badalamenti, Fabio; Garofalo, Germana; Carlström, Julia; Piwowarczyk, Joanna; Rabaut, Marijn; Vanaverbeke, Jan; Schipper, Cor; et al.
Abstract: A generic framework (FW) for the monitoring and evaluation of spatially managed areas (here defined as marine areas subject to a planning and management regime) was developed and tested in nine marine areas of 13 European countries under the EU funded project MESMA (Monitoring and Evaluation of Spatially Managed Areas). This paper describes the lessons learned in the use of the FW and draws conclusions for its future use and development. The selected case studies represented diverse spatial scales, management status and complexity, ranging from sub-national areas to entire national coastlines, and large offshore regions. The application of the FW consisted of seven steps: starting with (i) context setting and (ii) gathering of relevant ecosystem information, human activities and management goals; it continues with (iii) indicator selection and (iv) risk assessment; and the final steps considers the (v) analysis of findings and (vi) the evaluation of management effectiveness, to end up with (vii) the revision and proposal of adaptation to current management. The lessons learnt through the application of the FW in the case studies have proved the value of the FW. However, difficulties rose due to the diversity of the nature and the different stages of development in planning and management in the case study areas; as well as, limited knowledge on ecosystem functioning needed for its implementation. As a conclusion the FW allowed for a flexible and creative application and provided important gap analyses. Highlights: A framework for MSP was tested in cases from arctic areas to the Mediterranean. The step by step approach was valuable even when available information was scars. The required causal connection between objectives and indicators of state was useful. The creativity required to test the flexible framework was an important gap analyses.